Sequence alignment : methods, models, concepts, and strategies - Rosenberg, Michael S., 1972- (University of California Press, 2009)
The sequencing of the human genome involved thousands of scientists but used relatively few tools. Today, obtaining sequences is simpler, but aligning the sequences-making sure that sequences from one source are properly compared to those from other sources-remains a complicated but underappreciated aspect of comparative molecular biology. This volume, the first to focus on this crucial step in analyzing sequence data, is about the practice of alignment, the procedures by which alignments are established, and more importantly, how the outcomes of any alignment algorithm should be interpreted.